Experimental research on gypsum-based mixtures containing recycled roofing tile powder at ambient and high temperatures - Durgun, Muhammed Yasin; Durgun, Muhammed Yasin (Elsevier Sci Ltd, 2021)
In this study, the properties of gypsum-based pastes and mortars containing recycled tile powder were investigated at ambient and high temperatures. For this purpose waste tiles were collected from demolition sites and ground. Two different sample groups, namely gypsum pastes and gypsum mortars, were produced. Both groups had their own reference sample that was produced using only gypsum, in addition to samples that were modified by using 10%, 20% and 30% recycled tile powder. The samples were exposed to 600 degrees C and 800 degrees C. Unit weights, mass losses, ultrasonic pulse velocities, bending strengths, compressive strength, volume changes and visual investigations were performed on the samples before and after they were exposed to the high temperatures. In addition, the apparent porosity, water absorption and thermal conductivity of the recycled tile powder containing gypsum-based mixtures were investigated. In order to investigate the microstructural changes of the mixtures, scanning electron microscopy examinations and XRD analyses were performed. The findings showed that the strength of the mixtures decreased with the addition of recycled tile powder. The apparent porosity and water absorption of the mixtures were found to increase. However, the presence of recycled tile powder enhanced mass loss, thermal conductivity and high temperature resistance. Furthermore, the volume changes resulting from high temperatures were significantly reduced by using the recycled tile powder. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Gypsum-Based Mortar; Gypsum-Based Paste; High Temperature; Roofing Tile Waste; Strength; Volume Change